Secret Seven Adventure - Blyton, Enid (London Hodder Children's Books, 2004)
A priceless pearl necklace has been stolen, and the Secret Seven witnessed the thief making his escape. But where has he hidden the necklace?
Keywords: Childern's Literature - Fiction : Adventure